Popcorn : bear story - Asch, Frank (New York : Parent's Magazine Press.)
Sam Bear invites his friends to an impromptu Halloween party and asks them to bring a treat.
Keywords: Popcorn--Fiction; Bears--Fiction; Halloween--Fiction